Live In Vivo Imaging of Plasmodium Invasion of the Mosquito Midgut - Nathanie Trisnadi (American Society for Microbiology, 2020)
ABSTRACT The mosquito midgut is a critical barrier that Plasmodium parasites must overcome to complete their developmental cycle and be transmitted to a new vertebrate host. Previous confocal studies with fixed infected midguts showed that ookinetes traverse midgut epithelial cells and cause irreversible tissue damage. Here, we investigated the spatiotemporal dynamics of ookinete midgut traversal and the response of midgut cells to invasion. A novel mounting strategy was established, suitable fluorescent dye combinations were identified and protocols optimized to label mosquito tissues in vivo, and live imaging protocols using confocal microscopy were developed. Tracking data showed that ookinetes gliding on the midgut surface travel faster and farther than those that remain in the lumen or those that have invaded the epithelium. Image analysis confirmed that parasite invasion and cell traversal occur within a couple of minutes, while caspase activity in damaged cells, indicative of cellular apoptosis, and F-actin cytoskeletal rearrangements in cells extruded into the gut lumen persist for several hours. This temporal difference highlights the importance of hemocyte-mediated cellular immunity and the mosquito complement system to mount a coordinated and effective antiplasmodial response. This novel in vivo imaging protocol allowed us to continuously observe individual ookinetes in live mosquitoes within the gut lumen and during cell traversal and to capture the subsequent cellular responses to invasion in real time for several hours, without loss of tissue integrity. IMPORTANCE Malaria is one of the most devastating parasitic diseases in humans and is transmitted by anopheline mosquitoes. The mosquito midgut is a critical barrier that Plasmodium parasites must overcome to complete their developmental cycle and be transmitted to a new host. Here, we developed a new strategy to visualize Plasmodium ookinetes as they traverse the mosquito midgut and to follow the response of damaged epithelial cells by imaging live mosquitoes. Understanding the spatial and temporal aspects of these interactions is critical when developing novel strategies to disrupt disease transmission.